2020
DOI: 10.1891/wfccn-d-20-00021
|View full text |Cite
|
Sign up to set email alerts
|

“We Are Together”: Operating Protocol and Preliminary Evaluation of a Telephone Line for the Support of Healthcare Professionals During the Covid-19 Pandemic

Abstract: ObjectiveThe aim of the present article is to present the operating protocol of this helpline, as well as preliminary results of its evaluation.BackgroundThe “We Are Together” telephone support helpline (TSH) was developed for the empowerment of healthcare professionals in view of the psychological distress associated with the Covid-19 pandemic.MethodsBased on a scoping literature review the steps for the development of the TSH included: (a) identification of the objectives of the TSH, (b) description of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This took several forms, such as science cafés, telephone hotlines, or other counseling services. One notable example was the "we are in this together" direct line of the Cyprus University of Technology (32). Even though this was originally conceived as a support service offered to healthcare professionals by the Department of Nursing of the University, records indicated that the majority of calls originated from students and community members.…”
Section: Discussionmentioning
confidence: 99%
“…This took several forms, such as science cafés, telephone hotlines, or other counseling services. One notable example was the "we are in this together" direct line of the Cyprus University of Technology (32). Even though this was originally conceived as a support service offered to healthcare professionals by the Department of Nursing of the University, records indicated that the majority of calls originated from students and community members.…”
Section: Discussionmentioning
confidence: 99%